Depictability of the upper gastrointestinal tract on forward‐viewing radial endoscopic ultrasonography versus standard upper esophagogastroduodenoscopy - Tesshin Ban; Yoshimasa Kubota; Takuya Takahama; Shun Sasoh; Tomoaki Ando; Makoto Nakamura; Takashi Joh (DEN Open, 2022)
Abstract Objectives Esophagogastroduodenoscopy (EGD) is a widely used modality for investigating the upper gastrointestinal (GI) tract, similar to endoscopic ultrasonography (EUS) for the pancreaticobiliary system. A recent and novel forward‐viewing radial EUS has potential as an EGD. However, this potential has not yet been evaluated and reported in the literature. We compared the depictability of the upper GI tract on EUS using a standard EGD. Methods This was a prospective study in a single session in an identical patient and it was conducted at a single center. Results Sixty‐nine participants were enrolled in this study. A forward‐viewing radial EUS revealed equivalent visualizing performance compared with the standard EGD, except for the retroflex view of the three angular areas. Depiction scores of the anterior wall, lesser curvature, and posterior wall of the angulus in the retroflex view in the forward‐viewing radial EUS were 1.94 (95% confidence interval [CI], 1.36–2.52), 2.03 (95% CI, 1.48–2.58), and 1.93 (95% CI, 1.35–2.50), respectively. These scores were significantly lower compared with those of standard EGD scores of 2.97 (95% CI, 2.86–3.08), 2.97 (95% CI, 2.86–3.78), and 2.96 (95% CI, 2.83–3.09], respectively; p < 0.001). The rate of full‐mark score in these three angular areas was significantly lower in the forward‐viewing radial EUS than in the standard EGD (21/69, 30.4%; 23/69, 33.3%; 21/69, 30.4% vs. 67/69; 97.1%, 67/69; 97.1%, 66/69; 95.7%, p < 0.001 for all). Conclusions Although forward‐viewing radial EUS has the potential to simultaneously investigate the upper GI and pancreaticobiliary systems, it is too early to introduce it for this purpose.